PROMOTING BLUE ECONOMY: FACTOR IDENTIFICATION AND MODEL DEVELOPMENT FOR MICRO SMALL & MEDIUM ENTERPRISES (MSME) IN BITUNG, NORTH SULAWESI: A RESEARCH PROPOSAL - Handoko, Liza; Sihombing, Sabrina O.; Layman, Chrisanty V. (Universitas Pelita Harapan, 2022)
As an archipelagic country, Indonesia has so much potential to promote a blue economy. The blue economy refers to industrialized fishery activities promoting and accelerating economic growth. In other words, this industrialization in the marine and fishery sector is the process of adding value to the productivity and production scale. The fishery sector is one of the main sectors contributing to Indonesia’s economic growth and is not a standalone sector. However, it also brings other sectors into motion, such as tourism. Furthermore, we would like to dive deep into the technology-based blue economy. This research proposal aims to identify inhibiting and supporting factors for the digitalization of SMEs in the fishery sector.Moreover, after gathering those factors, this research will continue to build a model that explains entrepreneurial self-motivation in promoting and hindering digitalization programs. Two important reasons that this research is necessary are, first, limited studies were trying to identify factors that cause the technology gap for the SMEs in the fishery sector. Secondly, developing a model of internal factors that promote and hinder SMEs from going digital, particularly in the blue economy. This research will be conducted in Bitung City, North Sulawesi, as the object of research due to the potential of natural resources in the fishery sector.